Sistem Penunjang Keputusan Penentuan Siswa Berprestasi Pada SMP N 1 Pugung Menggunkan Metode AHP (Analytical Hierarchy Process) - Fransiska, Hera (Cerdika: Jurnal Ilmiah Indonesia, 2021)
Decision-making in an institution/school is very important. The principal should make a decision based on calculations and long-term thinking so that the decision to determine the outstanding students to be taken is not wrong. Learning achievement is a description of a student’s success rate in learning. The achievements they get can be in the form of academic and non-academic achievements. All of these are included in the criteria for students who are considered outstanding. To assist in determining students who are considered outstanding, a Decision Support System is needed. Determination of the students mentioned above can be categorized as a multicriteria case because there are several factors that cause various alternative choices with different values, so technology is needed to determine student achievement using the AHP (Analytical Hierarchy Process) method to help homeroom teachers manage assessments in order to make decisions appropriately. The purpose and objective of this research are to study the process of determining outstanding students with a manual system into a computerized system so as to facilitate the process of determining outstanding students.